INTERACTIVE WAYS OF TEACHING VOCABULARY FOR MIDDLE-CLASS STUDENTS - Botirova Zebo Xakimjon kizi,Abdigopporova Moxinur Bahodir kizi (Ethiopian International Journal of Multidisciplinary Research, 2025)
This article examines the effectiveness of interactive methods in increasing the vocabulary of middle school students (grades 5-9) . Vocabulary is important in language learning and directly affects students' thinking, communication, and writing skills. The paper analyzes how modern interactive methods - such as team and collaborative learning, brainstorming, Venn diagrams, mind mapping, using technologies such as mobile applications and online platforms - can help increase vocabulary. The results show that interactive methods in modern education increase students' motivation, allow them to learn new words faster, and use them actively. The study also suggests that interactive strategies can positively direct students' independent thinking and communication skills .